Peran Etika Digital dalam Upaya Penguatan Pendidikan Karakter di Era Digital - Ainia, Dela Khoirul (PAKAR Pendidikan, 2024)
The increasingly massive use of digital technology has influenced the process of life, one of which is in the field of education. Digital technology has been widely used in the learning process from the elementary to university levels. The use of technology also needs to be accompanied by strengthening character education, which can be done through understanding digital ethics. Digital ethics provides an understanding of moral standards and rules that can be carried out to utilize digital technology. Strengthening character education through digital ethics in the current era is necessary because the teaching and learning process uses more digital technology. The research method used is a literature study approach with descriptive analysis. This study aims to provide an understanding of the contribution of digital ethics applied in daily life to character education in the digital era. The results show that digital ethics has a role in efforts to strengthen character education in the digital era. This is shown through applying moral standards and rules that must be carried out in digital activities. So that applicable rules can direct all digital activities. Digital ethics is one aspect of strengthening character education in the increasingly advanced digital technology development era. If digital ethics is applied correctly, it will positively impact life in the future